ANALISIS HUBUNGAN ANTARA ENTERPRISE RESOURCE PLANNING DENGAN EFEKTIVITAS PENGENDALIAN INTERNAL PADA SEKTOR PERBANKAN - Teguh Puspandoyo (Universitas Jember, 2015)
Development of information technology in the sector of accounting has been think out an integrated system called Enterprise Resource Planning (ERP). In Indonesia, this system has been adopted by some commercial banks. This paper discusses the relationship between ERP with the effectiveness of internal controls through the case study on the banking sector. This is done because of the discovery of the problem regarding the number of cases of fraud and bank percing caused by weak internal controls, although some banks have implemented ERP that one of the benefits is to increase the effectiveness of internal control. The purpose of this paper is to provide evidence related to previous studies that comes from the journal of information systems and accounting journals related to ERP implementation and internal controls. Data collection method in this paper is the study of the documentation from the accounting literature and information systems. From the analysis, there are five factors that play a role similar in the success of the implementation of the ERP system and increase the effectiveness of internal controls. The solution to overcome the problem of internal controls in the banking sector which is using the five critical success factors above coupled with the strengthening of the role of the Internal Audit Unit. The final conclusion is that the factor of leadership support, employees, business processes, employee education, corporate management, and strengthening the role of Internal Audit can improve the effectiveness of internal control of a bank that has implemented ERP.